Nonnegligible Seroprevalence and Predictors of Murine Typhus, Japan - Tetsuro Aita; Eiichiro Sando; Shungo Katoh; Sugihiro Hamaguchi; Hiromi Fujita; Noriaki Kurita (Emerging Infectious Diseases, 2023)
To elucidate the epidemiology of murine typhus, which is infrequently reported in Japan, we conducted a cross-sectional study involving 2,382 residents of rickettsiosis-endemic areas in Honshu Island during August–November 2020. Rickettsia typhi seroprevalence rate was higher than that of Orientia tsutsugamushi, indicating that murine typhus is a neglected disease.